National uptake of jets E-portfolio. (13th March 2011) - Sinha, A; Dowler, K; Valori, R; Dunckley, P
Abstract : Introduction: JAG released the JETS e- portfolio in September 2009. Many trusts across the UK have adopted it allowing their trainees to log their endoscopic experience. The e-portfolio acts as a detailed electronic logbook, supports training, supports ARCP's and will be the main portal for application for JAG certification. Methods: Data is collected regularly on a national basis to monitor the uptake of the e-portfolios, number of lists, procedures, DOPS, trainees added, etc. This data can be analysed at a regional, trust wide or deanery wide basis. Here we present the current national uptake data at the time of writing (21 st November 2010). Results: 76.2% of the trusts in UK have been set up to use the JETS e-portfolio now as compared to 34.6% in March this year. 55.6% of trusts are actively using the system. 8905 procedures and 854 DOPS were logged last month. Of the total 2479 users of e-portfolio, 857 are trainees. 16 355 endoscopy lists have been logged, of which 5517 were dedicated training lists. 70 516 procedures have been recorded to date. There have been no major IT setbacks and the overall feedback from trainees using the system has been excellent. Conclusion: Nearly 12 months after its release, 76.2% of the trusts in UK have set up the JETS e-portfolio and 55.6% are actively using it. This steady uptake across the UK shows that the service finds this a valuable tool. We expect 100% uptake by March 2011. Up to date UK-wide data will be presented. Continued uptake is crucial as application for JAG certification through the JETS e-portfolio will begin in early 2011. There will be a grace period of 6 months where both online and paper logs can be used to obtain certification, but the online process through JETS e-portfolio will be the only means to gain JAG certification thereafter. The details of these are available on JAG website.